Legal Protection for Victims of Body Shaming Through Social Media from a Victimology Perspective - Debora Novayanti, Hasibuan, Ester Taruli; Dana Sugama, I Dewa Gede (Westscience Press, 2025)
The present existence of information technology dramatically affects people's lives. Technology with all the programs and conveniences offered makes it possible for people to be able to use the technology. Its users often ignore security for themselves. Cyberbullying is an immoral act committed through electronic media, one of which is body shaming. Body Shaming is an aggressive and repeated behavior by individuals and groups to comment on a person's body shape by using electronic technology as a medium to attack others. Body shaming cannot continue to be left alone because the impact the victim has can damage one's mental health and is also dangerous because it can be done anywhere and anytime. With the main discussion on this study, Do Legal Protection Forms Against Victims of Body Shaming Crimes on Social Media and Urgency of Legal Protection for Victims of Body Shaming Crimes on Social Media. Research results show that legal protection against victims of body shaming crimes on social media can be seen from the provisions of Law No. 1 13 of 2006, LPSK Regulation Number 6 of 2010, and article 27 paragraph 3 of the ITE Law. However, the current regulations are not yet effective in solving the body shaming problem on social media.